The relationship between Business Process Management and Knowledge Management - selected aspects from a study of companies in Poland - Agnieszka Bitkowska (Journal of Entrepreneurship, Management and Innovation)
The integration of the concepts of Business Process Management (BPM) and Knowledge Management (KM) is a challenging research issue today, and should be analyzed jointly in contemporary enterprises. The challenge for modern process organizations is the constant accumulation of knowledge and its skillful use in order to gain a competitive advantage and ensure a stable position in the market. Despite the growing interest among researchers and practitioners there is a lack of articles in this area. The main objective of this paper is to identify the relation between Business Process Management and Knowledge Management. The article presents the results of empirical research conducted by the author in contemporary enterprises in Poland in 2019, and some solutions, as well as benefits, related to the correlation of these two concepts. Business Process Management has a positive influence over Knowledge Management processes. The identification, acquisition, presentation and documentation of knowledge are not independent tasks, but are implemented within processes. The implementation of Knowledge Management stimulates employee creativity and supports internal communication. Building a process organization using best practices and guidelines minimizes the risk of failure of projects to improve the organization and implement Knowledge Management. In order to test the correlations between them, Yule’s, Pearson’s, and Bykowski’s coefficients have been used.